Community-Based Sociodemographic Determinants of Chemotherapy Response in Breast Cancer: A Retrospective Study from Central Java, Indonesia - Jauhari Deslo Angkasa Wijaya; John Sammy Leids Alfawin Peter; Nilam Smaradhania; Berti Julian Nelwan; Imeldy Prihatni Purnama; Putra Agina Widyaswara Suwaryo (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Breast cancer remains a major global health concern, with disparities in treatment outcomes often rooted in social inequalities. Sociodemographic factors such as education, economic status, social support, and healthcare access play critical roles in influencing how patients respond to neoadjuvant chemotherapy (NAC). Understanding these determinants is essential for designing effective, community-based health promotion strategies that address health disparities. This study aimed to examine the influence of sociodemographic factors on breast cancer patients’ response to NAC and to explore implications for community health promotion. Method: A retrospective quantitative study was conducted on 144 breast cancer patients who received NAC at PKU Muhammadiyah Hospital Gombong, a secondary-level healthcare facility in Central Java, Indonesia. Statistical analyses were performed using SPSS version 28. Data on education level, economic status, social support (assessed via the MOS Social Support Survey), and healthcare access (measured by distance to facility) were collected. Treatment responses were categorized as complete, partial, or progressive. Statistical analysis involved chi-square, Mann-Whitney U, and multinomial logistic regression to determine significant predictors of response. Result: Patients with lower education levels were 2.50 times more likely to have a partial response (p = 0.031) and 4.20 times more likely to experience a progressive response (p = 0.004). Low economic status increased the likelihood of partial (OR = 3.30, p = 0.003) and progressive responses (OR = 6.40, p = 0.001). Each additional kilometre from a healthcare facility raised the risk of partial (OR = 1.20, p = 0.002) and progressive responses (OR = 1.50, p = 0.001). Higher social support decreased the odds of progressive response by 30% (OR = 0.70, p < 0.001). Social inequalities—particularly related to education, income, distance to care, and social support—significantly affect treatment response among breast cancer patients undergoing NAC. Consulasion: This study fills a gap in the existing literature by utilizing real-world, community-based data to examine chemotherapy response through a health equity lens, moving beyond biologically centered models. It contributes theoretically by aligning findings with the social determinants of health framework, offering insights into structural disparities in cancer care. These findings emphasize the urgent need for integrated health promotion interventions aimed at improving health literacy, strengthening community support systems, and reducing structural barriers to care. Empowering underserved populations through community-based strategies is essential for equitable cancer outcomes.